2003
DOI: 10.1103/physrevb.68.060401
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and magnetic structure ofLaTiO3:Evidence for nondegeneratet2g

Abstract: The crystal and magnetic structure of LaTiO3 has been studied by x-ray and neutron diffraction techniques using nearly stoichiometric samples. We find a strong structural anomaly near the antiferromagnetic ordering, TN =146 K. In addition, the octahedra in LaTiO3 exhibit an intrinsic distortion which implies a splitting of the t2g-levels. Our results indicate that LaTiO3 should be considered as a Jahn-Teller system where the structural distortion and the resulting level splitting are enhanced by the magnetic o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
227
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(262 citation statements)
references
References 18 publications
32
227
1
2
Order By: Relevance
“…These parameters give the low-spin 4 A 1 and 4 E excitations close to 4.5 eV, in agreement with experiment. 28 So the above values of the microscopic parameters ͕U , J H ͖ appear to [76][77][78][79] and to the Mott transition 80 -here we do not intend to discuss this controversial issue.…”
Section: Optical Spectral Weights In Lamnomentioning
confidence: 99%
“…These parameters give the low-spin 4 A 1 and 4 E excitations close to 4.5 eV, in agreement with experiment. 28 So the above values of the microscopic parameters ͕U , J H ͖ appear to [76][77][78][79] and to the Mott transition 80 -here we do not intend to discuss this controversial issue.…”
Section: Optical Spectral Weights In Lamnomentioning
confidence: 99%
“…The original idea is due to Mochizuki and Imada, who considered the t 2g -level splitting in the Ti-compounds associated with the displacements of Y and La sites. 23 It was paraphrased by Cwik et al, 12 who suggested the main effect comes from the deformation of the TiO 6 octahedra. A more general picture has been considered by Schmitz et al, 24 who summed up all contributions in the Madelung potential.…”
Section: Model Hamiltonianmentioning
confidence: 99%
“…6 for YTiO 3 (the data corresponds to the temperature T=293 K), in Ref. 12 for LaTiO 3 (T=8 K), in Ref. 14 for YVO 3 (T=65 K and 100 K, for the orthorhombic and monoclinic phase, respectively), and in Ref.…”
Section: Crystal and Magnetic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…[152,161] On SrTiO 3 , both materials are grown under compressive strain. For a single LaTiO 3 -LaFeO 3 lattice, it is hard to distinguish the crystal structure by XRD.…”
Section: Crystal Structurementioning
confidence: 99%